Micro Fine Sized Palm Oil Fuel Ash Produced Using a Wind Tunnel Production System. (5th September 2016) - Ahmadi, R.; Zainudin, N.; Ismail, I.; Mannan, M. A.; Abidin, A. S. Z.
Abstract : Micro fine sized palm oil fuel ash (POFA) is a new supplementary cementitious material that can increase the strength, durability, and workability of concrete. However, production of this material incurs high cost and is not practical for the construction industry. This paper investigates a simple methodology of producing micro fine sized POFA by means of a laboratory scale wind tunnel system. The raw POFA obtained from an oil palm factory is first calcined to remove carbon residue and then grinded in Los Angeles abrasion machine. The grinded POFA is then blown in the fabricated wind tunnel system for separation into different ranges of particle sizes. The physical, morphological, and chemical properties of the micro fine sized POFA were then investigated using Laser Particle Size Analyser (PSA), nitrogen sorption, and Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM-EDX). A total of 32.1% micro fine sized POFA were collected from each sample blown, with the size range of 1–10 micrometers. The devised laboratory scale of wind tunnel production system is successful in producing micro fine sized POFA and, with modifications, this system is envisaged applicable to be used to commercialize micro fine sized POFA production for the construction industry.